Deoxyribonuclease activities in Lactobacillus delbrueckii - Azcárate Peril, M. A. (2000)
DNase activity was examined in the extracellular and subcellular fractions of six non-transformable strains belonging to Lactobacillus delbrueckii subsp. lactis (L. lactis) and Lactobacillus delbrueckii subsp. bulgaricus (L. bulgaricus) and compared with the activity present in Lactobacillus johnsonii NCK 65, a transformable strain of Lactobacillus. In the extracellular fraction of the L. delbrueckii strains, a common protein band of 36 kDa was detected, while a band of 29 kDa was found in the same fraction of L. johnsonii. No nuclease activity was detected in the cytoplasmic fraction of this strain, indicating that the localization of the DNase activity could be a key factor in the uptake of foreign DNA.